Percutaneous treatment of aorto-ostial coronary lesions: Current challenges and future directions. (1st May 2015) - Jaffe, Ronen; Halon, David A.; Shiran, Avinoam; Rubinshtein, Ronen
Abstract: Flow-limiting aorto-ostial coronary lesions are clinically important because they subtend a large myocardial territory and may induce extensive myocardial ischemia. Diagnosis and treatment of these lesions is challenging and procedural success and clinical outcomes are inferior to non-ostial lesions. The purpose of this review is to summarize current knowledge regarding aorto-ostial percutaneous coronary intervention and to suggest novel approaches for optimizing these procedures. Highlights: Stenting of aorto-ostial coronary lesions is challenging and outcomes are inferior to non-ostial lesions. Angiography is a suboptimal method for guiding these procedures. Inaccurate stent positioning may be a major cause for suboptimal outcomes of aorto-ostial interventions. Several novel technologies have been designed to address these issues.